KNOWLEDGE, SKILLS, ABILITIES AND OTHER REQUIREMENTS FOR ISLAMIC LEGACY PLANNERS - Shahizan Md. Noh (Journal of Islamic, Social, Economics and Development, 2020)
Legacy planners providing Islamic legacy planning solutions that have relevant knowledge are needed to serve better the clients. These legacy planners who are termed as Islamic legacy planners require a different set of knowledge to become competent in performing their responsibilities efficiently. This paper aims to explore the specific elements of knowledge, skills, abilities and others (KSOA) required of Islamic legacy planners in performing their responsibilities efficiently. A multiple-case study involving the full-fledged Islamic trust companies in Malaysia has been conducted to gather insights on current practices of recruiting Islamic legacy planners and determine the relevant KSOA for the profession. The findings reveal that fiqh mawarith as the primary knowledge to be acquired besides knowledge in the other areas. This study finds that Islamic legacy planner must also have the willingness to learn attitude as a complementing characteristic to the knowledge and skill elements identified above, as a package required for a competent Islamic legacy planner. This research contributes to the management policy in the recruitment or training of Islamic legacy planners in the full-fledged Islamic trust companies in Malaysia.